Establishment of an indicator system for assessing public health emergency response capacity at county/district level : a Delphi study - Yalin ZHOU; Yixin ZHANHG; Xinyu TIAN; Yang HAN; Chengxi SUN; Jingyu MA; Qun LI; Zhen XU; Jixiang MA (Zhongguo gonggong weisheng, 2023)
ObjectiveTo establish a set of indicators for assessing the public health emergency response capacity at county/district level in China. MethodsAn indicator system for evaluating public health emergency response capacity at county/district level was initially formulated based on theoretical research and literature review. Three rounds of Delphi consultation were conducted among 18 senior professionals to determine the indicators and their weights of the system using hierarchical analysis method. ResultsFor the 3 rounds of expert consultation, the positive coefficients of the were 100.0%, 88.9%, and 88.9%; the expert authority coefficients were 0.87, 0.84, and 0.87; and the coordination coefficients of expert opinions were 0.207, 0.210, and 0.295 (all P < 0.001), indicating a good coordination of the experts′ opinions. The finally established indicator system for assessing public health emergency response capacity at county/district level included 5 first-, 19 second-, and 61 third-level indicators. For the third round of Delphi consultation, the experts′ mean scores and ranges of coefficients of variance for importance/feasibility of all the indicators were 4.83 ± 0.13/4.48 ± 0.21 and 0.00 – 0.18/0.07 – 0.22, respectively. The weights for the first-, second-, and third-level indicators ranged from 0.094 to 0.290, 0.011 to 0.119, and 0.001 to 0.087, respectively. ConclusionThe established indicator system could be used to develop tools for evaluating public health emergency response capacities at county/district level, while the reliability and validity of the indicator system need to be assessed further.